2022
DOI: 10.1039/d2an01327d
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in small molecular near-infrared fluorescence probes for a targeted diagnosis of the Alzheimer disease

Abstract: Nowadays, it is still quite challenging to achieve early diagnosis of Alzheimer's disease (AD) in clinic. The burgeoning near-infrared fluorescence (NIRF) imaging fulfills the requirements for precise diagnosis with good...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 170 publications
0
36
0
Order By: Relevance
“…AD is a neurological disease, which is difficult for diagnosis in early stage. [43] It is reported that Cu 2+ level in brain is correlated with the development of AD. Wang et al designed a series of molecular probes (RPS1-RPS4) in response to Cu 2+ for PA imaging from "off" to "on" (Figure 1c).…”
Section: (4 Of 19)mentioning
confidence: 99%
“…AD is a neurological disease, which is difficult for diagnosis in early stage. [43] It is reported that Cu 2+ level in brain is correlated with the development of AD. Wang et al designed a series of molecular probes (RPS1-RPS4) in response to Cu 2+ for PA imaging from "off" to "on" (Figure 1c).…”
Section: (4 Of 19)mentioning
confidence: 99%
“…3 Excessive ONOO − can oxidize multiple molecules or produce highly reactive secondary free radicals, 4 leading to structural modification and dysfunction of proteins, 5 nucleic acids, 6 and lipids 7 and producing significant cytotoxic consequences. In addition, an abnormally high level of ONOO − is also related to many diseases, such as neurodegenerative diseases, 8,9 inflammatory infections, 10,11 liver injury diseases, 12,13 and even cancer, 14 as well as influencing the endoplasmic reticulum viscosity. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…3 Excessive ONOO − can oxidize multiple molecules or produce highly reactive secondary free radicals, 4 leading to structural modification and dysfunction of proteins, 5 nucleic acids, 6 and lipids 7 and producing significant cytotoxic consequences. In addition, an abnormally high level of ONOO − is also related to many diseases, such as neurodegenerative diseases, 8,9 inflammatory infections, 10,11 liver injury diseases, 12,13 and even cancer, 14 as well as influencing the endoplasmic reticulum viscosity. 15,16 At present, several methods for detecting ONOO − have been reported, such as near-infrared spectroscopy, 17,18 high-performance liquid chromatography, 19 chemiluminescence, 20 fluorescence spectroscopy, [21][22][23] ultraviolet-visible absorption spectroscopy, 24 electron spin resonance 25,26 and electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Near-infrared sensors have been developed rapidly due to their characteristics of causing low damage, low background fluorescence, and deep tissue penetration. 39–54…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Near-infrared sensors have been developed rapidly due to their characteristics of causing low damage, low background fluorescence, and deep tissue penetration. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Herein, we designed a near-infrared probe NRH-800 (Scheme 1), which uses rhodamine derivatives as a fluorescent nuclear component to modify the positively charged indole rings that tend to be enriched in mitochondria and the transdouble bond of probe molecules, which can be cut by HClO to trigger fluorescence changes. NRH-800 can thus meet the demands of imaging in the near-infrared fluorescence mode and has a sufficiently large emission shift.…”
Section: Introductionmentioning
confidence: 99%